Design for Recycling Strategies Based on the Life Cycle Assessment and End of Life Options of Plastics in a Circular Economy. Issue 13 (3rd May 2022) - Venkatachalam, Venkateshwaran; Pohler, Merlin; Spierling, Sebastian; Nickel, Louisa; Barner, Leonie; Endres, Hans‐Josef
Abstract: The plastic economy, despite offering unique properties in fulfilling the functions of products in different industrial sectors over decades, has so far been mainly linear, that is, "take‐make and dispose" with only a small fraction of plastics being recycled worldwide. With ever‐increasing circular economy initiatives and the urge to conserve resources and prevent plastic pollution from affecting ecosystems, more emphasis on the resource recovery of plastic products after its use has been made over the last few years. It is necessary for manufacturers to understand the value chain as early as the design phase while manufacturing and distributing plastic products across the world. The current study provides an overview of the status quo of plastic waste management and analyzes the Life Cycle Assessment (LCA) studies of different End‐of‐Life (EoL) options for plastics. Based on the LCA studies, a preliminary, country‐specific Circular Footprint (CF) is calculated and Design for Recycling (DfR) strategies are identified. Results show that the environmental impacts of different EoL options differ significantly for different plastics. The CF highlights the lack of data regarding the composition and recovery of plastics in different countries thus showing the necessity to consider the whole lifecycle when quantifying the environmental impacts of plastics. Abstract : To understand the environmental impacts of treating plastic wastes, a review on the Life Cycle Assessment (LCA) studies of End‐of‐Life (EoL) options of different plastic types is conducted. A preliminary Circular Footprint (CF) for treating plastic wastes in different countries is calculated from the environmental impacts. Based on these results, Design for Recycling (DfR) strategies are identified in this study.